PENGGUNAAN MEDIA PAPAN PINTAR DALAM MATERI KEUTUHAN NKRI UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS BELAJAR SISWA KELAS IV DI SD NEGERI PETERONGAN SEMARANG - Danang Kusuma, Alfan; Ayu Nyoman Murniati, Ngurah; Winarni Alexsandri, Luthfi; Agustini, Ferina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to determine the effect of using Smart Board media assisted by wordwall applications on learning PPKn in improving learning outcomes and learning activities of fourth grade students at SD Negeri Peterongan Semarang. The type of research used is a quantitative experiment using Group Pretest-Posttes design. The population of this study were 27 IVA class students. This research data was obtained through student learning outcomes (Pretest-Posttes) and observation of student learning activities. The results showed that student learning outcomes had improved. It can be seen from the difference in the average score of pretest 68.70 and posttest 88.33. The hypothesis results obtained through the paired sample test (t test) show a significance value of 0.000 <0.05, meaning Ho is rejected and Ha is accepted. The average results conducted through the gain test obtained 0.65 into the high category, meaning that there is an effect of using Smart Board media assisted by wordwall application to improve the learning outcomes of fourth grade students of SD Negeri Peterongan Semarang. The results showed that the data obtained on student learning activeness was very good 24 students with a percentage of 89% and 3 students had good learning activeness with a percentage of 11% in using the Smart Board media.